Legal adaptation of Palestinian resistance in the Gaza Strip In the light of the rules of public international law - Doughan, Mohamad Mahmoud (Journal of Economic, Administrative and Legal Sciences, 2024)
Palestinian resistance, whether military or civilian in the Gaza Strip, is central to the Israeli-Palestinian conflict and has a significant impact on the political and security situation in the region. The sector is being subjected to several Israeli wars and attacks, and Palestinian resistance is returning with its armed operations, leading to an escalation of tension and violence in the region. The Palestinian resistance in the Gaza Strip is adopting an armed resistance strategy, using several means and tactics in the face of Israeli occupation. These include the firing of rockets and into Israeli territory, the carrying out of explosions and the targeting of Israeli occupying forces and settlements, as well as the use of popular protests, demonstrations and marches as tools to express demands and resistance. All of this has led the Zionist entity to consider that the actions of the Palestinian resistance in the Gaza Strip are acts of terrorism that have no international cover or protection. The perpetrators must therefore be held accountable before the Israeli courts. This is contrary to reality, considering that the Gaza Strip is a Palestinian territory and that the actions of the Palestinian resistance are a response to the ongoing attacks by the Israeli enemy army. Here, the importance of research lies in giving proper adaptation to the Palestinian resistance in the Gaza Strip so that it can enjoy the international protection of the Geneva Conventions and the norms of international law and that anyone arrested during the Israeli aggression is a prisoner of war because what the Palestinian resistance is doing in the Gaza Strip is dedicated to the right of peoples to defend themselves and to free their destiny under occupation.